Efficacy of Toona sureni Merr. leaf extract against Aedes spp. and Culex spp. by electric diffusion - Sulasmi Sulasmi; Budirman Budirman; Haderiah Haderiah; La Taha; Nurhaidah Nurhaidah (Institute of Advanced Engineering and Science, 2026)
Aedes spp. and Culex spp. mosquitoes are major vectors of dengue fever and filariasis. The extensive use of chemical insecticides has contributed to resistance and environmental concerns, underscoring need for eco-friendly alternatives. Suren leaf extract (Toona sureni Merr.) contains bioactive compounds with potential as a botanical insecticide. This study evaluates suren leaf extract delivered via an electric diffusion device for indoor adult mosquito control at concentrations of 45%, 55%, and 65% against Aedes spp. and Culex spp. A post-test-only control group design was applied with three replications, and outcomes were recorded over a 60 minutes exposure period. Mortality increased with both concentration and exposure time. At 60 minutes, mortality increased from 80% to 100% in Aedes spp. and from 64% to 96% in Culex spp. when the concentration increased from 45% to 65%. Two-way analysis of variance (ANOVA) confirmed significant effects of concentration and exposure time (p <0.001). These findings indicate that electric diffusion delivery of suren leaf extract is effective and supports its potential use for indoor vector control in endemic areas.